Dinosaur swim tracks from the Lower Cretaceous of La Rioja, Spain: An ichnological approach to non-common behaviours. (July 2023) - Navarro-Lorbés, P.; Díaz-Martínez, I.; Valle-Melón, J.M.; Rodríguez-Miranda, Á.; Moratalla, J.J.; Ferrer-Ventura, M.; San Juan-Palacios, R.; Torices, A.
Abstract: The reconstruction of behavioural patterns performed by non-avian dinosaurs is an important task of palaeontology in order to globally understand how these animals interacted with their environment. Their relation with aquatic lifestyles has always been an intriguing question that has been extensively studied during the last decades, especially focused on some specific groups. The present work describes a new tracksite with 27 swimming tracks located in a fluvial setting from the Lower Cretaceous Urbion Group of La Rioja (Spain). They are preserved as natural casts with sizes between 8.5 and 29.2 cm and a predominant orientation. The tracks have been classified into 6 different morphotypes according to their morphology, and grouped into 5 different categories depending on the different pes-substrate interactions, following the proposal of Romilio et al. (2013). Some tracks were produced while the animal was moving in partial or complete buoyancy, and displacement was conducted by water and sediment impulsion, not just a mere paddling. Other tracks could be impressed in a bottom-walked, when the trackmaker touched the digit tips on the ground vertically or sub-vertically. This new tracksite confirms the capabilities of some groups of non-avian dinosaurs to interact with shallow water environments where they could print their pedes as they moved, either in complete buoyancy or during a displacement with some vertical component in the water column. It also contributes to the better understanding of swimming track morphologies as especially dependent on pes-sediment interaction and environment more than differences in pes configuration itself, causing the high variability of swimming footprints even when they belong to the same trackway. The classification of swimming tracks and footprints into categories dependent on the pes-substrate interaction could be a good guiding principle to avoid problematics about ichnotaxonomical definition.